(3CgejI GdUdGI aj MjGI GdeSdes - (3YHO Gddg, GdSjO YHO GdMcjes; (3gjFI cHGQ YdeGA GdLeYjI GdTQYjIs ((3GdbGgQI(B[(3eUQ(B]s (3GdeDSSI GdYQHjI GdMOjKIs, 1988)
(3GdUdI ef Cge hChd GdYHGOGJ GdJj CeQfG Gddg HgG, hdgG ahGFO LneI hefGaY YXjeI, jLH Ydj cd eSde Cf jYdegGs
4 6 16
Keywords: (3GdUdGIs; (3GdabI GdESdGejs